(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Wound healing property of Sida corymbosa plant leaves was investigated. Standard procedures were then used to investigate the phytochemical constituents and the antibacterial activity of the extracts. Alkaloid, saponins, flavonoids, terpenoids, tannins and steroids were detected in the plant extracts. All the phytochemicals detected in the plant extracts were present in the methanol extract with the exception of steroids. Antibacterial activity showed zone of inhibitions that ranged between 10 mm and 21 mm. The methanol extract especially inhibited the growth of Staphylococcus aureus, Pseudomonas aeruginosa and Streptococcus pyogenes at MIC of 25 mg/ml. The MBC for the methanolic extract on Staphylococcus aureus was 100 mg/ml whereas the MBC for Pseudomonas aeruginosa and Streptococcus pyogenes was 50 mg/ml. It can be concluded from this research work that Sida corymbosa leaves is a good source of antibacterial agents that possess wound healing property in line with its ethno-medicinal use.